Diet and sexual dimorphism of liophis poecilogyrus (serpentes, dipsadidae) from the wetland regions of Northeast Argentina - Prieto, Yanina (2012)
Feeding ecology is one of the most important aspects in the life history of snakes; however, studies about their trophic ecology are scarce and sometimes inaccurate. Liophis poecylogyrus is a medium-sized snake distributed widely in South America and relatively abundant in the study area. We describe the diet and sexual dimorphism of L. poecilogyrus from northeast Argentina based on the examination of museum specimens, and we compare our data with studies that include representative samples of this species. Amphibians were the most frequent prey (75), but only one reptile was found (1). Families represented were: Bufonidae (53), Leiuperidae (19), Leptodactylidae (14), Hylidae (7), Cycloramphidae (3), Microhylidae (2), and Gymnophthalmidae (2). We observed that L. poecilogyrus has significant sexual size dimorphism in all morphometric characters analyzed but not in scalation variables. Despite the fact that L. poecilogyrus is considered by some to be an omni-carnivore, our data and other quantitative studies on distant populations from South America lead us to suggest that this species eats primarily anurans. The population studied has its own characteristics but retains similarities with geographically nearby and remote populations. This species is a specialist and its feeding habits seem to be conservative both in different populations of the same species and in phylogenetically related species. Sexual size dimorphism may be a common feature of the taxonomic group.